Seroprevalence and detection of Human herpesvirus-8 (HHV-8) among healthy blood donors residing in Qatar - Hadeel T. Zedan; Alaa Elkhider; Asalet Hicazi; Fathima Amanullah; Duaa W. Al-Sadeq; Parveen B. Nizamuddin; Farah M. Shurrab; Maria K. Smatti; Asmaa A. Althani; Laith J. Abu Raddad; Gheyath K. Nasrallah; Hadi M. Yassine (Journal of Infection and Public Health)
Background: Human herpesvirus 8 (HHV-8) is a critical causative agent behind Kaposi sarcoma (KS), an oncogenic disease with profound consequences in immunocompromised individuals. Studies suggested HHV-8 seroprevalence in healthy populations is uncommon, but comprehensive investigations within the Middle East region remain scarce. This study aimed to bridge this knowledge gap by meticulously assessing HHV-8 seroprevalence among healthy blood donors in Qatar, leveraging serological methodologies and PCR. Methods: We used sera samples collected from 621 healthy blood donors (median age = 36 years, IQR 30–43) from different nationalities residing in Qatar, mainly from the MENA region and Southeast Asia. All sera samples were tested for total anti-HHV-8 IgG antibodies using ELISA. The presence of lytic HHV-8 antibodies was confirmed by an immunofluorescence assay (IFA). Further, HHV-8 DNA was tested and quantitated by qRT-PCR. Results: ELISA detected anti-HHV-8 IgG total antibodies in 6.9 % [43/621, 95 %CI 5.2–9.2] of the tested samples. Subsequent testing by IFA revealed that 14 % [6/43, 95 %CI 3.6–24.3] of these anti-HHV-8 IgG were classified as HHV-8 lytic antibodies. This suggests that 0.97 % [6/621, 95 %CI 0.2–1.7] of these donors had a recent or ongoing active infection and viral replication. Only one seronegative Qatari blood donor had detectable HHV-8 DNA in his blood. No significant difference was observed between HHV-8 seropositivity and the demographic characteristics of the donors. Conclusion: Our study showed that HHV-8 prevalence in Qatar aligns closely with global reports. Moreover, our findings raise considerations regarding HHV-8’s potential transmission via transfusion, which suggests the value of routine HHV-8 screening, particularly for immunocompromised patients vulnerable to KS.